2013
DOI: 10.1246/cl.131005
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management by Organisms of the Phototoxicity of Chlorophylls

Abstract: . His research interests span from the elucidation of photosynthetic energy and electron transfer in a molecular level using natural systems and artificial models to the construction of photoactive nano(bio)devices. AbstractThe phototoxic effects of chlorophylls on the cells of organisms have been debated for decades. The extreme phototoxicity of uncontrolled chlorophylls and the concomitant need for rapid elimination of chlorophylls in cells have again attracted attention since the robust processes of higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…(, ) found that herbivorous protozoa produce cPPB‐ a E when they graze on and digest microalgae. cPPB‐ a E is generated from pyropheophytin a (Kashiyama and Tamiaki ). Several types of phytoplankton are also able to generate cPPB‐ a E (Kashiyama et al.…”
Section: Discussionmentioning
confidence: 99%
“…(, ) found that herbivorous protozoa produce cPPB‐ a E when they graze on and digest microalgae. cPPB‐ a E is generated from pyropheophytin a (Kashiyama and Tamiaki ). Several types of phytoplankton are also able to generate cPPB‐ a E (Kashiyama et al.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Kashiyama and Tamiaki (2014) published a review, which described various strategies by which organisms avoid phototoxicity of chlorophylls, emphasizing the costs of adaptive mechanisms against this risk of these biological processes. The objective of the present study was to evaluate the potential risk of environmental toxicity caused by the application of chlorophyll to control pest organisms in aquatic systems.…”
mentioning
confidence: 99%
“…The observed phylogenetic ubiquity of CACC among eukaryotes strongly indicates that the acquisition of CACC was a key evolutionary step that led to the diversity of extant eukaryotes. CACC is a “rate-emphasizing” process [6] that is rapid and requires no substantial biochemical cost and thus advantageous in digestive processing of algal materials. On the other hand, another “quality-emphasizing” process [6], such as the phyllobilin/PAO pathway, is rigorously but only slowly degrading chlorophylls with substantial biochemical costs (i.e., in the consumption of reducing cofactors and ATP); hence, it is less suited for algivorous processing.…”
Section: Discussionmentioning
confidence: 99%
“…However, the elevated p O 2 conditions of the modern world are a major potential source of oxidative stress (if not death) to organisms. Moreover, molecular oxygen is even destructive when it is photosensitized by “phototoxic” biomolecules, such as chlorophylls [6].…”
Section: Introductionmentioning
confidence: 99%